2002
DOI: 10.3136/fstr.8.291
|View full text |Cite
|
Sign up to set email alerts
|

Functional Improvements in Food Proteins in Multiple Aspects by Conjugation with Saccharides: Case Studies of .BETA.-Lactoglobulin-Acidic Polysaccharides Conjugates.

Abstract: Many studies on the conjugates of proteins and saccharides (neoglycoproteins) have been carried out over the past 20 years to improve the function of proteins. However, most have been carried out by attachment or elimination of low-molecular weight molecules for single purposes. The structure-function relationship of the conjugates has not been well understood, and little is known about the improvement of proteins by conjugation with polysaccharides. We sought to achieve functional improvements in food protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 70 publications
1
26
0
Order By: Relevance
“…In the food industry, protein-polysaccharide conjugates are useful because of improved functional properties over proteins [6][7][8][9][10][11]. Conjugates have improved heat and pH stability, solubility, emulsification, and gelation properties and may offer lower astringency and allergenicity compared to unmodified proteins [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In the food industry, protein-polysaccharide conjugates are useful because of improved functional properties over proteins [6][7][8][9][10][11]. Conjugates have improved heat and pH stability, solubility, emulsification, and gelation properties and may offer lower astringency and allergenicity compared to unmodified proteins [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…To achieve such multiple functional improvements, we have been studying on the neoglycoconjugates of BLG. Studies on the neoglycoconjugates of proteins have been widely investigated during the last 30 years, 6) and various improvements in the function of proteins have been achieved. We have shown that improved emulsifying properties [7][8][9] and reduced immunogenicity [10][11][12] of BLG could be achieved by conjugating with carboxymethyl dextran.…”
Section: Functional Improvements To -Lactoglobulin By Preparing An Edmentioning
confidence: 99%
“…We have been studying the neoglycoconjugates of BLG to achieve this. 7) Protein conjugation can simultaneously achieve reduced allergenicity and improved functional properties (such as thermal stability, solubility, and emulsifying ability) while maintaining the physiological functions of proteins. We focused our previous studies on the neoglycoconjugates of BLG.…”
mentioning
confidence: 99%
“…We focused our previous studies on the neoglycoconjugates of BLG. BLG was conjugated with carboxymethyl dextran 7) or chitosan by means of a water-soluble carbodiimide 8) and with acidic oligosaccharides (alginic acid oligosaccharides or phosphoryl oligosaccharides) by the Maillard reaction. 9) We also prepared the conjugates by DNA recombinant technology 10) and by using microbial transglutaminase.…”
mentioning
confidence: 99%